Decolonizing Mormonism : approaching a postcolonial Zion - Colvin, Gina; Brooks, Joanna, 1971- (Salt Lake City : The University of Utah Press, 2018)
"This volume seeks nothing less than to shift the focus of Mormon studies from its historic North American, Euro-American "center" to the critical questions being raised by Mormons living at the movement's cultural and geographic margins. As a social institution, Mormonism is shaped around cultural notions, systems, and ideas that have currency in the United States but make less sense beyond the land of its genesis. Even as an avowedly international religion some 183 years out from its inception, it makes few allowances for diverse international contexts, with Salt Lake City prescribing programs, policies, curricula, leadership, and edicts for the church's international regions. While Mormonism's greatest strength is its organizational coherence, there is also a cost paid, for those at the church's peripheries. Decolonizing Mormonism brings together the work of 15 scholars from around the globe who critically reflect on global Mormon experiences and American-Mormon cultural imperialism. Indigenous, minority, and Global South Mormons ask in unison: what is the relationship between Mormonism and imperialism and where must the Mormon movement go in order to achieve its long-cherished dream of equality for all in Zion? Their stories are both heartbreaking and heartening and provide a rich resource for thinking about the future of Mormon missiology and the possibilities inherent in the work of Mormon contextual theology"--Provided by publisher.
Introduction : approaching a postcolonial Zion / Gina Colvin and Joanna Brooks -- A Maori Mormon testimony / Gina Colvin -- Decolonization on the Salish Sea : a tribal journey back to Mormon studies / Thomas Murphy -- Porter Rockwell and Samuel the Lamanite fistfight in heaven : a Mormon Navajo filmmaker's perspective / Angelo Baca -- "This is the place!" : disrupting Mormon settler colonialism / Elise Boxer -- Unpacking white-heritage Mormon privilege : a Latter-Day Saint pursuit of critical consciousness / Rolf Straubhaar -- An abundant God knows the middle also / Alicia Harris -- What I learned at girls camp, or Developing a racial identity leads to liberation / Mica McGriggs -- Empowering Latino saints to transcend historical racialism : a bishop's tale / Ignacio Garcia -- Mormonism as colonialism, Mormonism as anti-colonialism, Mormonism as minor transnationalism : historical and contemporary perspectives / Joanna Brooks -- The LDS church in Flanders : their way, our way, or their way in our own way / Ingrid sherlock -- Sister acts : relief society and flexible citizenship in Hong Kong / Stacilee Ford -- A tale of three primaries : the gravity of Mormonism's informal institutions / Melissa Wei-Tsing Inouye.
Includes bibliographical references and index.
Print version record and CIP data provided by publisher; resource not viewed.
Added to collection customer.56279.3 - Master record variable field(s) change: 072
Keywords: Church of Jesus Christ of Latter-day Saints -- Doctrines; Church of Jesus Christ of Latter-day Saints; Globalization -- Religious aspects -- Church of Jesus Christ of Latter-day Saints; Globalization -- Religious aspects -- Mormon Church; Mormon Church -- Doctrines; Church and minorities; Church and minorities; Mormon Church -- Doctrines; Theology, Doctrinal; RELIGION / Christianity / Denominations; Electronic books